Knowledge and attitude towards basics of communication skills amongst resident doctors - Chavan, Kalidas D.; Giri, Purushottam A.; Mumbre, Sachin S.; Bangal, Rajendra S. (International Journal of Research in Medical Sciences, 2019)
Background: The pillar of doctor patient relationship is the bond of mutual trust. This pillar is strengthened by effective communication between doctor and patient/relatives. It has been widely accepted that a doctor needs to have very good communication skills in addition to clinical knowledge and skills required for effective healthcare. Every doctor duly needs to demonstrate humanity, healthy behaviour, as well as sensible communication with patients which can build the sustainable ‘trust’ in the treatment offered by that doctor. However, the current curriculum of medical courses is enormously focused on providing competent medical knowledge but lacking the focus on inculcating communication skills. Methods: A cross sectional study was carried out amongst 377 resident doctors of first to third year, from randomly selected medical colleges of Maharashtra having postgraduate courses in clinical subjects and affiliated to Maharashtra University of Health Sciences, Nashik, Maharashtra, India during the period of February 2017 to January 2019. Data was entered in MS Excel sheet and analyzed using percentages and proportions wherever appropriate. Results: Highest study respondents were from General Medicine with 13% of total and having 17.4% males and 8% females among respective genders followed by General surgery and Pediatrics residents with 12.5% each specialty. Conclusions: The study has shown that there was varied knowledge about the communication skills among the resident doctors. The residents have shown fair attitudes and behaviours towards mindfulness and basic communication skills.